Etika Batuk Penderita Tuberkulosis Dengan Kejadian Penularan Penyakit Pada Keluarga - Erfan Rofiqi; Caturia Sasti Sulistyana (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Objective: Tuberculosis is an infection of the respiratory tract caused by mycobacterium tuberculosis through droplets when coughing, sneezing, talking, or laughing that often occurs in the elderly. One coughing person produces 3,000 sputum sputum. Patients who have not been identified can be a source of transmission to those around them. One of the preventive measures for transmission of tuberculosis is the application of cough ethics. The purpose of this study was to analyze the relationship of cough ethics with transmission of tuberculosis to families in the Sidotopo Wetan Health Center Surabaya areajMethods: The design of this study was cross sectional in a sample of 36 tuberculosis patients with a simple random sampling technique. Analysis of this research data used Chi Square test.Results: The statistical test results obtained P value 0.014 (α<0.05), it meanis that there is a relationship between the ethics of cough and transmission of tuberculosis to the family.Conclusion: Cough ethics is a good and correct procedure for coughing to prevent the spread of tuberculosis germs through droplets, namely by using a mask, disposing of tissue into the trash, washing hands with clean water and soap, covering the mouth and nose when coughing, removing saliva or phlegm in the room shower or in a closed place filled with antiseptic fluid. The wrong behavior of coughing ethics can transmit the disease to the surrounding people. The implication of this study is the application of good and correct cough ethics can reduce the risk of transmission of tuberculosis in family members who have not been infected with tuberculosis.